Correlações entre alguns caracteres agronômicos da soja (Glycine max (L) Merrill) nas gerações F5 e F6 - de Oliveira , Aluízio B; Sediyama, Tuneo; Sediyama, Carlos S; S Reis , Múcio; Silva , José Carlos (Revista Ceres, 2025)
Aiming to estimate the fenotypic correlations among the main agronomic traits of soybean, the behavior of F5 and F6 lines of ‘Parana’ x ‘UFV-1’ and TAC-2’ X ‘UFV-1’, crosses were studied in the growing seasons of 1981/82 and 1982/83, at Viçosa and Capinépolis, in the State of Minas Gerais.